Traditional uses of plants in Gokwe South District, Zimbabwe: construction material, tools, crafts, fuel wood, religious ceremonies and leafy vegetables - Bridgett Shopo; Ruvimbo J. Mapaya; Alfred Maroyi (Department of Ethnobotany, Institute of Botany, Ilia State University, Tbilisi, Georgia, 2023)
Abstract